Utilizing Mathematical Models as a Basis for Coffee Cultivation Techniques - Tanti Novita; Venti Novita Sari; Risa Oktaria; Lisa Malinda (Cita konsultindo, 2025)
Coffee cultivation is an agricultural sector that requires a scientific approach to increase productivity and efficiency. The use of mathematics in agricultural management is still rarely applied systematically, even though various studies show that number-based analysis can help optimize resources. The integration of mathematical concepts in coffee farming can be a solution in facing the challenges of climate change and crop yield uncertainty. This research aims to examine how the application of mathematics can increase efficiency in cultivating coffee plants. The main focus of this research is quantitative analysis of water management, fertilizer distribution, and crop yield predictions based on mathematical models. This study also assesses the impact of using calculation methods on farmers' economic stability and environmental sustainability. This research uses a quantitative approach with survey methods and case studies on several coffee farming groups in Indonesia. Data was obtained through direct observation, interviews, and statistical analysis of production patterns and crop distribution. Simple mathematical models are used to measure the effectiveness of irrigation planning, fertilizer application, and crop stock management. The research results show that farmers who apply a mathematics-based approach experience an increase in productivity of up to 20% compared to traditional methods. More efficient resource management also has an impact on reducing operational costs and increasing resilience to external factors such as weather and market price fluctuations. Integration of prediction models helps farmers make more precise decisions regarding planting and harvest times. This research concludes that the application of mathematics in coffee farming contributes to increasing efficiency, environmental sustainability and farmer welfare. Education and training regarding calculation-based methods are important steps to expand the application of this strategy. Further studies are needed to develop more complex models with the integration of digital technology to increase the precision of analysis in coffee cultivation.